2010
DOI: 10.1002/pssc.201000429
|View full text |Cite
|
Sign up to set email alerts
|

Exciton behaviours in doped tris (8‐hydroxyquinoline) aluminum (Alq3) films

Abstract: The doping effect on exciton behaviours in amorphous tris (8‐hydroxyquinolinato) aluminum (Alq3) were studied for the first time by transient photoluminescence (PL) measurements at room temperature. The dopants 4‐(diacynomethylene)‐2‐methyl‐6‐(p‐dimethylaminostyryl)‐4H‐pyan (DCM) and 5,6,11,12‐tetraphenylnaphthacene (rubrene) were used into Alq3 films at various concentration from 0.5 to 24 wt.% for this study. The exciton recombination rate was found sharply increased with doping concentration in Alq3 films. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
1
2
Order By: Relevance
“…The corresponding fitted luminescence lifetimes are within 0.2 ns for the measured range of pressures. This is in contrast to previous time-resolved DCM doping PL studies, where the lifetime significantly decreased with increased DCM concentration, due to the exciton quenching by aggregated dye molecules. This comparison highlights that the solvatochromic shift due to change in density in organic matrix under pressure does not exhibit the pronounced aggregation quenching effect on exciton lifetime.…”
Section: Resultscontrasting
confidence: 99%
“…The corresponding fitted luminescence lifetimes are within 0.2 ns for the measured range of pressures. This is in contrast to previous time-resolved DCM doping PL studies, where the lifetime significantly decreased with increased DCM concentration, due to the exciton quenching by aggregated dye molecules. This comparison highlights that the solvatochromic shift due to change in density in organic matrix under pressure does not exhibit the pronounced aggregation quenching effect on exciton lifetime.…”
Section: Resultscontrasting
confidence: 99%
“…The early works show that rubrene promotes electron transporting in [Alq 3 :(coumarin 6, rubrene)] (Alq 3 co-doped with coumarin 6 and rubrene) [10]. In [Alq 3 :rubrene], it was also found that rubrene promotes excimer diffusion coefficient but decreases diffusion length and life-time [11]. In this study, our results indicate that rubrene doping in Alq 3 slightly impedes electron transporting.…”
Section: Resultscontrasting
confidence: 35%
“…This bilayer-structure WOLED shows quite simple configuration of ITO/ hole-injection layer/ hole-transport-and-blue-emitting layer (HT-BEML)/electron-transportand-yellow-green-emitting layer (ET-YEML)/electron-injection layer/ cathode. 5,6,11,12-tetraphenylnaphthacene (rubrene) doped tris(8-hydroxy-quinolinato)aluminum (Alq 3 ), [Alq 3 :rubrene], is one of the most widely-used yellow-green emitter for its excellent emitting efficiency and film morphology [9][10][11][12]. Consequently, the electron transporting characteristics play a crucial role in bilayer-structure WOLED with [Alq 3 :rubrene] as ET-YEML.…”
Section: Introductionmentioning
confidence: 99%